Arguing for Argument’s Sake? Exploring Public Conversations around Climate Change on Twitter - Kennedy Mayfield-Smith; Alexa Lamm; Fallys Masambuka-Kanchewa; Abigail Borron; Jessica Holt (Journal of Applied Communications, 2021)
Audience-facilitated information flow has become the new norm created by a public divergence from traditional media sources. Mobile device advancements and partnerships have changed how audiences view news media and the sources relied upon to obtain information. With these advancements, social media users have become primary information providers and information gatekeepers. Twitter specifically has become a news media platform for some based on its effectiveness in facilitating information flow and triggering reorganization as it provides a platform for collaboration and coordination. Despite widespread acceptance of the threat climate change poses by the scientific community, it is still a topic of contention on social media. Climate conversations are typically approached with an us versus them mindset with us being used as representation of the communities to which audiences belong. The communities one belongs to typically follows social media users social, political and environmental ideologies. Walton’s theory of argument or inference schemes served as the theoretical framework for this study. Argument schemes represent common arguments and special context arguments, in this case scientific argumentation. Walton’s argument from ignorance was used as a framework for the study. The argument states that if there has been a thorough search through the knowledge base then concrete proof of a fact would exist. The findings indicated social media may be a useful tool when exploring climate change conversations through a sociopolitical lens and additional research is needed to closely examine how political ideologies, global location, and different environmental topics impact issue awareness and beliefs.
Keywords: : climate change; Twitter; public engagement; argumentation theory; climate communication